Próba identyfikacji pozarynkowych ekonomicznych stymulatorów ochrony środowiska - Bartniczak, Bartosz (Off-Market Economics Stimulators of Environmental Protection, 2008)
The main aim of this article is to show off market, economic stimulators of environmental protection. These factors are used by the government to encourage environmentally friendly behavior of entrepreneurs. Among these stimulators are: state aid and ecological taxes. This article presents their characterization, and tries to answer the following question: which stimulator is better?
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 76-83